Polymorphism at the Clock gene predicts phenology of long‐distance migration in birds. Issue 8 (3rd April 2015) - Saino, Nicola; Bazzi, Gaia; Gatti, Emanuele; Caprioli, Manuela; Cecere, Jacopo G.; Possenti, Cristina D.; Galimberti, Andrea; Orioli, Valerio; Bani, Luciano; Rubolini, Diego; Gianfranceschi, Luca; Spina, Fernando
Abstract Dissecting phenotypic variance in life history traits into its genetic and environmental components is at the focus of evolutionary studies and of pivotal importance to identify the mechanisms and predict the consequences of human‐driven environmental change. The timing of recurrent life history events (phenology) is under strong selection, but the study of the genes that control potential environmental canalization in phenological traits is at its infancy. Candidate genes for circadian behaviour entrained by photoperiod have been screened as potential controllers of phenological variation of breeding and moult in birds, with inconsistent results. Despite photoperiodic control of migration is well established, no study has reported on migration phenology in relation to polymorphism at candidate genes in birds. We analysed variation in spring migration dates within four trans‐Saharan migratory species (Luscinia megarhynchos; Ficedula hypoleuca; Anthus trivialis; Saxicola rubetra) at a Mediterranean island in relation to Clock and Adcyap1 polymorphism. Individuals with larger number of glutamine residues in the poly‐Q region of Clock gene migrated significantly later in one or, respectively, two species depending on sex and whether the within‐individual mean length or the length of the longer Clock allele was considered. The results hinted at dominance of the longer Clock allele. No significant evidence for migration date to covary with Adcyap1 polymorphism emerged. This is the first evidence that migration phenology is associated with Clock in birds. This finding is important for evolutionary studies of migration and sheds light on the mechanisms that drive bird phenological changes and population trends in response to climate change.